If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -3) + 4x + 8 = 3(4 + -3x) + 12x + -9 Reorder the terms: -2(-3 + x) + 4x + 8 = 3(4 + -3x) + 12x + -9 (-3 * -2 + x * -2) + 4x + 8 = 3(4 + -3x) + 12x + -9 (6 + -2x) + 4x + 8 = 3(4 + -3x) + 12x + -9 Reorder the terms: 6 + 8 + -2x + 4x = 3(4 + -3x) + 12x + -9 Combine like terms: 6 + 8 = 14 14 + -2x + 4x = 3(4 + -3x) + 12x + -9 Combine like terms: -2x + 4x = 2x 14 + 2x = 3(4 + -3x) + 12x + -9 14 + 2x = (4 * 3 + -3x * 3) + 12x + -9 14 + 2x = (12 + -9x) + 12x + -9 Reorder the terms: 14 + 2x = 12 + -9 + -9x + 12x Combine like terms: 12 + -9 = 3 14 + 2x = 3 + -9x + 12x Combine like terms: -9x + 12x = 3x 14 + 2x = 3 + 3x Solving 14 + 2x = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 14 + 2x + -3x = 3 + 3x + -3x Combine like terms: 2x + -3x = -1x 14 + -1x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 14 + -1x = 3 + 0 14 + -1x = 3 Add '-14' to each side of the equation. 14 + -14 + -1x = 3 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 3 + -14 -1x = 3 + -14 Combine like terms: 3 + -14 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| -4*3/17 | | 7x-15=4x+13 | | 0.30x+0.20(150)=0.15(110) | | Ac=7x-15 | | 5x-7+10x-8=180 | | x^2+24x+320=0 | | W=-0.5v | | x-(x-4)=8 | | -6=17+x | | .5x+10=14.5 | | 3x+y=2x+33 | | 3/2(x-4)=7/6 | | lny+10y-4=0 | | 2x=3x-45 | | 10+5(z-2)=-2z+2 | | (x+20)(x-6)(13x+7)= | | 2/3=8W | | -4.2x+3.5y+2.6-5.9x-2.4y= | | 10+5z(z-2)=-2z+2 | | 2w=4/3 | | x^2-4=8x | | 5k+20-3-3k=7k | | -5/(-2)=x | | .8(x+20)+.2x=41 | | 178.7-176.9= | | 2(x+2)-9=3x-19 | | 15x+y+.25z=100 | | 2*3+4-36= | | 10x+18y=700 | | (1/3)9.9.9 | | 4(x+1)+(2x-7)=50 | | f(x)=x*x-6 |